2019
DOI: 10.1080/01434632.2019.1595632
|View full text |Cite
|
Sign up to set email alerts
|

The inclusion process of young Romanians in Catalonia (Spain): the relationship between participating in classes of L1, self-identification, and life-satisfaction

Abstract: The inclusion process of young Romanians in Catalonia (Spain): The relationship between participating in classes of L1, self-identification, and life-satisfaction We analyse the influence of attending or not attending classes of the language of origin in self-identification and in life-satisfaction. In addition, we analyse how these elements are related to the perception of integration of young immigrants of Romanian origin in a multilingual and multicultural context like that of Catalonia (Spain). We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This is consistent with the existing literature linking systemic discrimination towards racialised groups and ethnic minorities with a higher prevalence of bullying at school (Bae et al, 2019;Fuentes Cabrera et al, 2019;Nikolaou et al, 2019). This has also been found within the Spanish school environment, where negative attitudes towards students of prevalent immigrant groups are present among other students and teachers (Petreñas et al, 2019;Serra et al, 2015;Serra i Salamé, 2001). Moreover, our findings regarding differences between first-generation immigrants and the children of immigrants are also supported by previous research.…”
Section: Exposure To Bullyingsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the existing literature linking systemic discrimination towards racialised groups and ethnic minorities with a higher prevalence of bullying at school (Bae et al, 2019;Fuentes Cabrera et al, 2019;Nikolaou et al, 2019). This has also been found within the Spanish school environment, where negative attitudes towards students of prevalent immigrant groups are present among other students and teachers (Petreñas et al, 2019;Serra et al, 2015;Serra i Salamé, 2001). Moreover, our findings regarding differences between first-generation immigrants and the children of immigrants are also supported by previous research.…”
Section: Exposure To Bullyingsupporting
confidence: 90%
“…Several studies conducted in Spanish schools show that teachers and students present particularly negative attitudes towards Moroccan culture (Petreñas et al, 2019; Serra et al, 2015; Serra i Salamé, 2001), which reflects wider societal discourses that target young Muslim people (especially boys) as a potentially dangerous group that must be under surveillance to prevent future terrorist activity (Choudhury, 2021). On the other hand, Muslim girls are typically characterised as victims of their own culture and subdued to their parents or male relatives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Soriano-Miras, Trinidad-Requena, and Guardiola [64] also concluded that older migrants had better perceptions of well-being. This idea was also supported by Petrañas and others [55], who stressed that relinquishing certain aspects of their roots may promote a sense of belonging. However, to explore this further, it would be necessary to conduct a cross-sectional study, analysing perceptions of satisfaction with life and inclusion among the same sample of the migrant population throughout their life or stay in the host country.…”
Section: Discussionmentioning
confidence: 75%
“…Regarding the age of the migrants, this study also concluded that older migrants have a better perception of well-being, and suggested that this could be attributed to the fact that "with age, immigrants put down roots, which helps generate this well-being" ([64], p. 649). This idea is supported by a recent study concluding that relinquishing certain aspects of one's roots may promote a sense of belonging while also exposing migrants to stressful and internal-conflictive situations [55].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation